P53 and erbB-2 Are Not Associated in Matched Cases of Primary and Metastatic Ovarian Carcinomas. Issue 1 (12th June 2013) - Rodríguez-Burford, Cristina; Chhieng, David C.; Stockard, Cecil R.; Kleinberg, Marc J.; Barnes, Mack N.; Partridge, Edward E.; Weiss, Heidi L.; Grizzle, William E.
Abstract : Ovarian cancer has a high mortality rate largely due to the limited number of ovarian carcinomas detected at an early stage. Understanding the molecular changes occurring during the progression of ovarian carcinoma would aid in the development of therapies that may inhibit or target metastasis. Primary and metastatic lesions from 54 and 40 patients with advanced ovarian carcinoma, respectively (including matched primary and metastatic lesions from 30 patients) were evaluated for nuclear accumulation of p53 (clone BP53-12-1) and cytoplasmic and membranous immunostaining of p185 erbB-2 (clone 3B5) by immunohistochemistry. No differences in the immunostaining of p53 and p185erbB-2 (cytoplasm or membrane) were observed between primary and metastatic lesions of the matched cases. Similarly, no differences in the proportion of positive cases of p53 between primary and metastatic lesions of the matched cases was observed. Thus, novel therapies that target p53 or p185erbB-2 can utilize specimens from either primary or metastatic lesions to characterize these targets prior to therapy. Spearman correlations between p53 and p185erbB-2 (cytoplasm or membrane) immunohistochemistry scores were insignificant for the matched cases, all primary lesions, and all metastatic lesions. Also, no significant associations occurred between nuclear accumulation of p53 (positive versus negative) and phenotypic expression of p185erbB-2 (cytoplasm or membrane) immunostaining scores for the matched cases, all primary lesions, and all metastatic lesions. Thus, the nuclear accumulation of p53 and immunostaining of p185erbB-2 in the cytoplasm or on the cellular membranes are independent.